2019
DOI: 10.1186/s41239-019-0131-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing students’ written production in English through flipped lessons and simulations

Abstract: Today, learning is perceived as a challenge that must be faced simultaneously on numerous fronts. Indeed, learning is no longer confined to the classroom. Students have the opportunity to learn inside and outside the classroom walls. Technology plays its part, as does the abundance of information available on social networks and in the mass media. Educators must stay abreast of change as information and potentially useful technological resources leave traditional education behind. Optimising class time through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…These students reported that the "flipped" classroom format supported their learning needs better than a traditional lecture and regarded it as more interactive. Ageline and Garcia-Cabonell [24] demonstrated that a flipped classroom format implemented in an undergraduate English literature classroom helped to improve students' writing skills in terms of organization and linking of ideas. Other recent studies have revealed that in a flipped classroom format, students have higher levels of motivation, as well as autonomy and self-regulation [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…These students reported that the "flipped" classroom format supported their learning needs better than a traditional lecture and regarded it as more interactive. Ageline and Garcia-Cabonell [24] demonstrated that a flipped classroom format implemented in an undergraduate English literature classroom helped to improve students' writing skills in terms of organization and linking of ideas. Other recent studies have revealed that in a flipped classroom format, students have higher levels of motivation, as well as autonomy and self-regulation [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies used quantitative methods (n = 11) for collecting the data, followed by mixed methods (n = 9), and one exploratory study. For the quantitative studies (n = 11), two of the studies used true experimental designs (Wu, 2015;Angelini & Carbonell, 2019), four studies used quasi-experimental designs (Alfadil, 2020;Chen & Lee, 2018;Chu, Wang, & Wang, 2019;Lin & Mubarok, 2021), and five used causal-comparative research (Ali, Segaran, & Hoe, 2015;Yang & Wu, 2015;Wei, Kao, Lu, & Liu, 2018;Chen, Chen, & Dai, 2018;Fu & Yang, 2019).…”
Section: Research Methods In the Studies Of The Implementation Of Edu...mentioning
confidence: 99%
“…Angelini and García-Carbonell (2019) performed a study to investigate whether simulation-based courses as a component of the flipped classroom model make a substantial contribution to the students’ progress in their written production in the English language. The results indicated that students in the experimental group who were educated by simulation-based courses were more likely to improve their skills at writing in the English language when compared with the students in the control group who were educated through the traditional education model.…”
Section: Literature Reviewmentioning
confidence: 99%